Lithuanian bourgeois reactionary educational policy influenced the contents of primary school reading books - Karčiauskienė, M. (Psichologija, 1962)
The bourgeois Lithuanian government began to actively fight the progressive movement in Lithuania from the early days of the Soviet withdrawal of government (1919). In the first year, when the bourgeois government did not feel strong and when the events 1918-1919 were still well remembered the government disguised its true aspirations. After the 1926 coup the fascist government in Lithuania began to operate openly. This was reflected in education. If The Lithuanian bourgeoisie declared political disengagement of schools before the fascist period, then after the fascist coup, it began to openly pursue their objectives of reactionary education. The clergy was a loyal assistant to the fascists. Children's civic and religious education was emphasized. The school policy was clearly reflected in reading books. This article shows how educational policy was reflected in reading books in elementary school. Nationalism was required from books until the Fascist period. They included excerpts from Valančius, Šatrijos Ragana, Kudirka, Žemaitė, Biliūnas, and Vincas Krėvė. Any number of recommended authors (such as Biliūnas and Žemaitė) were valuable works from both a literary and ideological perspective. But reading books already did not just foster national feeling in this period, but also developed humility and expressed class contradictions; the reality is often portrayed in a distorted. After the fascist coup a direct task was assigned to reading books: to educate children in a narrow nationalist and clericalist spirit. Since 1927 every textbook has been checked by the Ministry of Education Commission before its release. Clergymen's influence on the books particularly intensified. Having experienced the fascist's and clergymen's pressure, a number of authors reinforced the clerical and fascist spirit in their books. The books of Vasiliauskas-Gerutis and Murka were in particular changed in this light. The reactionary Rinkūnas reading book appeared. Fascists and clerics strongly attacked the author who insufficiently adapted to the requirements of reactionaries. However the books were not popular among progressive teachers and the reactionaries of Lithuanian society. Progressive books by Esmaitis and Jakučiūnas increasingly spread in teaching practice. Such reactionary books as Rinkūnas's "Aukuras" (Alter) and Murka's "Naujas Darbas" (New Work) did not spread in teaching practice, and Vasiliauskas-Gerutis's reading book "Rūtelė" was even derided in the educational press. In this way reactionary bourgeois public policy in schools received resistance from progressive educators and Lithuanian society.
Keywords: reading books and history of pedagogy